L-Arginine Enhances Intracellular Killing of Carbapenem-Resistant Klebsiella pneumoniae ST258 by Murine Neutrophils - Hernán F. Peñaloza; Danielle Ahn; Bárbara M. Schultz; Alejandro Piña-Iturbe; Liliana A. González; Susan M. Bueno (Frontiers in Cellular and Infection Microbiology, 2020)
Carbapenem-resistant Klebsiella pneumoniae ST258 (CRKP-ST258) are a global concern due to their rapid dissemination, high lethality, antibiotic resistance and resistance to components of the immune response, such as neutrophils. Neutrophils are major host mediators, able to kill well-studied and antibiotic-sensitive laboratory reference strains of K. pneumoniae. However, CRKP-ST258 are able to evade neutrophil phagocytic killing, persisting longer in the host despite robust neutrophil recruitment. Here, we show that neutrophils are unable to clear a CRKP-ST258 isolate (KP35). Compared to the response elicited by a prototypic K. pneumoniae ATCC 43816 (KPPR1), the neutrophil intracellular response against KP35 is characterized by equivalent production of reactive oxygen species (ROS) and myeloperoxidase content, but impaired phagosomal acidification. Our results ruled out that this phenomenon is due to a phagocytosis defect, as we observed similar efficiency of phagocytosis by neutrophils infected with KP35 or KPPR1. Genomic analysis of the cps loci of KPPR1 and KP35 suggest that the capsule composition of KP35 explain the high phagocytosis efficiency by neutrophils. Consistent with other reports, we show that KP35 did not induce DNA release by neutrophils and KPPR1 only induced it at 3 h, when most of the bacteria have already been cleared. l-arginine metabolism has been identified as an important modulator of the host immune response and positively regulate T cells, macrophages and neutrophils in response to microbes. Our data show that l-arginine supplementation improved phagosome acidification, increased ROS production and enhanced nitric oxide consumption by neutrophils in response to KP35. The enhanced intracellular response observed after l-arginine supplementation ultimately improved KP35 clearance in vitro. KP35 was able to dysregulate the intracellular microbicidal machinery of neutrophils to survive in the intracellular environment. This process, however, can be reversed after l-arginine supplementation.